Effect of nozzle exit shape on the geometrical features of horizontal turbulent jet flame. (15th January 2020) - Zhou, Kuibin; Wang, Yuzhu; Zhang, Le; Wu, Yueqiong; Nie, Xuan; Jiang, Juncheng
Highlights: New correlation is built for the flame geometry of horizontal jet fire of shape-different exits. The exit shape coefficient dominates the phenomenological constant of flame length correlation. Richardson number dominates the upward tilt of horizontal jet flame. A revised dimensionless flow number is proposed to fit the lift-off distance. Abstract: The accidental releases of high pressure gas fuel could lead to the jet fires, resulting in a serious of disastrous events. This paper presents a systematical investigation upon the effect of nozzle exit shape on the horizontal jet flame geometry by experiments. The nozzles of circular, rectangular, equilateral triangle and elliptic exits were used for experimental tests. New correlations for the horizontally projected flame length, vertically projected flame height and lift-off distance are established for horizontal jet fires ejected from the exits of different shapes. The exit shape coefficient (the ratio of hydraulic to equivalent diameters) is found to dominate the phenomenological constant in the classic correlation of flame length, and the dependency of phenomenological constant on exit shape coefficient is quantified. It is also clarified that Richardson number (the ratio of flame buoyancy to exit momentum) dominates the ratio of vertically projected flame height to horizontally projected flame length. The hydraulic diameter is proposed to revise the dimensionless flow number, for physically addressing the effect of exit shape on the lift-off distance of horizontal jet flame.